RETRACTED: Distance learning as a means of forming subjective attitude in physically challenged children - Bayborodova Lyudmila; Serebrennikov Lev; Shipkova Ekaterina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001